Alternative postmeniscectomy regimen. Issue 6161 (17th February 1979) - Sergeant, T; Edwards, A
Abstract : Eighty patients who had undergone routine meniscectomy were divided into two groups for postoperative management. The first 40 patients were treated by the traditional method of a compression bandage with a backsplint, followed by a 10-day stay in hospital. In the other 40 patients a compression bandage was applied, reinforced by a plaster cylinder. Weight-bearing was allowed with the aid of crutches, and patients were discharged after four days in hospital. Adequate splintage and early ambulation was more convenient and comfortable for postoperative management, and no complications ensued. Less time was needed for physiotherapy, and earlier return to work and resumption of normal activities were made easier.